2001
DOI: 10.1556/aalim.30.2001.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Methanol Feed Strategies for Recombinant Pichia Pastoris Mut S Fermentation

Abstract: Methylotrophic yeast Pichia pastoris is an ideal host organism for recombinant protein production. However, adequate methanol feed is still a critical point of successful product formation in P. pastoris Mut 5 fermentations. Three methanol feed strategies were tested: an organic vapor sensor, a dissolved oxygen controlled methanol addition and a predetermined model, as well. The organic vapor sensor proved to be unsuitable for methanol concentration measurements when samples were taken from the head space of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
2
16
0
2
Order By: Relevance
“…Therefore, we suggested that the optimal methanol concentration in the media is ranging from 0.5% to 1.0%. Compared with the methanol concentration, there were fewer reports on YNB and initial cell density [30]. Like with the previous study, our results clearly showed that YNB did not have significant effect on recombinant xylanase production.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, we suggested that the optimal methanol concentration in the media is ranging from 0.5% to 1.0%. Compared with the methanol concentration, there were fewer reports on YNB and initial cell density [30]. Like with the previous study, our results clearly showed that YNB did not have significant effect on recombinant xylanase production.…”
Section: Discussionsupporting
confidence: 64%
“…In some cases, metabolism-related method is preferred , and in other cases, nonmetabolism-related method, in which the growth rate can be controlled, is preferred (Zhang et al, 2000a). However, detailed comparisons of various fedbatch strategies for the production of a specific recombinant protein are very limited (Kupcsulik et al, 2001;Minning et al, 2001;Zhang et al, 2000b). Our purpose here is to evaluate several growth strategies for the production of extracellular murine endostatin.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of methanol conversion determines the available energy and carbon for maintenance, cell growth, product formation and product transport into the media. Overall productivities for cell mass and HSA (human serum albumin) showed similar dependence on methanol concentration as the specific rates (Kupcsulik & Sevella, 2004).…”
Section: Resultsmentioning
confidence: 82%